The Role Of Oral Dysfunctıons On The Development Of Dental Malocclusıon In The Normal And Mentally-Retarded Chıldren - Murat Sipahier; Neşe Akal; Alev Alaçam (Galenos Yayinevi, 1992)
In this investigation, the role of oral dysfunctions on the development of dental malocclusion were discussed in 50 normal and 50 mentally-retarded children whose ages were above 12 years. In both groups, number of children who has dental malocclusion and their dispertion according to malocclusion types were evaluated. The effect of oral disfunctions on the development of malocclusion and the incidance of malocclusion was found statistically important in the mentally-retarded rather than normal children.